A case of post-traumatic anterior cranial dural arteriovenous fistula - Vishal Bhasme; Divya Jain; Lomesh Bhirud (Egyptian Journal of Neurosurgery)
Abstract Introduction Dural arteriovenous fistula (dAVF) is an abnormal connection between an artery supplying the brain and vein or a venous sinus draining it. They account 10–15% of total arteriovenous malformations and are mostly idiopathic. Acquired cases include recurrent cerebral venous sinus thrombosis, head trauma, and past brain surgery. Case report A 41 years old admitted for severe headache, vomiting, and right-sided weakness. Patient had history of head trauma 3 years back. Radiology revealed left frontal hematoma with left anterior ethmoidal artery supplying a fistula and vein draining into left frontal parafalcine region with sac. Patient underwent craniotomy with clipping of dAVF without any major post-operative events. Conclusion Development of dAVF following trauma is rare. Our patient did not have any significant event in the past but developed dAVF as sequelae after 3 years. Anterior dAVF pose a challenge for endovascular embolization but clipping is straightforward.